PLANNING OF WASTEWATER TREATMENT PLANTS IN THE TAPIOCA FLOUR INDUSTRY USING ANAEROBIC FILTER UPFLOW SYSTEM (UAF) (Case Study of Mojoagung Village, Trangkil District, Pati Regency) - Mohammad Debby Rizani; Farida Yudaningrum; Kukuh Wisnuaji Widiatmoko; Fiki Nur Fitriani; Eka Silvi Nur Fianty; Intan Mayasari (Faculty of Engineering, Universitas Islam Darul Ulum Lamongan, 2026)
Mojoagung Village, Trangkil District, Pati Regency, is one of the major tapioca flour production areas in Central Java, Indonesia. The wastewater generated from tapioca processing is commonly discharged directly into nearby rivers without adequate treatment, causing unpleasant odors, low pH levels, and environmental pollution that may disturb the aquatic ecosystem. This study aimed to design a Wastewater Treatment Plant (WWTP) for the tapioca flour industry using an Upflow Anaerobic Filter (UAF) system combined with biofilter media consisting of bioballs, honeycomb media, and pumice stone. The research employed a quantitative analytical method based on wastewater quality testing and hydraulic design calculations. The parameters analyzed included Biochemical Oxygen Demand (BOD), Chemical Oxygen Demand (COD), Total Suspended Solids (TSS), cyanide (CN), and pH. The laboratory results indicated that the BOD, COD, and TSS concentrations met the wastewater quality standards, while the CN and pH parameters did not comply with the applicable standards due to acidic conditions and noticeable discoloration. Based on the design calculations, the proposed WWTP requires a land area of 29.28 m³ with dimensions of 18.3 m in length, 1.6 m in width, and 2.5 m in depth. The estimated construction cost of the WWTP was Rp 69,959,471.109. The proposed UAF-based treatment system is expected to reduce environmental pollution and improve the management of wastewater generated from tapioca flour production.